Far1 and Fus3 link the mating pheromone signal transduction pathway to three G1-phase Cdc28 kinase complexes. - Tyers, M (1993)
In the yeast Saccharomyces cerevisiae, the Cdc28 protein kinase controls commitment to cell division at Start, but no biologically relevant G1-phase substrates have been identified. We have studied the kinase complexes formed between Cdc28 and each of the G1 cyclins Cln1, Cln2, and Cln3. Each complex has a specific array of coprecipitated in vitro substrates. We identify one of these as Far1, a protein required for pheromone-induced arrest at Start. Treatment with alpha-factor induces a preferential association and/or phosphorylation of Far1 by the Cln1, Cln2, and Cln3 kinase complexes. This induced interaction depends upon the Fus3 protein kinase, a mitogen-activated protein kinase homolog that functions near the bottom of the alpha-factor signal transduction pathway. Thus, we trace a path through which a mitogen-activated protein kinase regulates a Cdc2 kinase.